2021
DOI: 10.3389/fphar.2020.593764
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Self-Medication Practice Among Teachers’ Education Training College Students in Amhara Region, Ethiopia: A Cross-Sectional Study

Abstract: Background: Self-medication practice is the use of medications without healthcare professional requests. It can lead to inappropriate medication usage, wastage of resources, increased chance of microbial resistance, and adverse drug reactions. Therefore, this study aimed at assessing the prevalence and associated factors of self-medication practice among teachers’ education training college students in the Amhara region, Ethiopia.Methods: A multicentre cross-sectional study was conducted on 344 teachers’ educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
14
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
7
14
2
3
Order By: Relevance
“…However, according to this study, self-medication practices (SMP) have been found to be significantly associated with a person's residence, and the prevalence of SMP is higher among people living in rural areas than people living in urban areas. This is in contrast to a study in Ethiopia that revealed that living in a city was strongly associated with selfmedication 28 . SMP was shown to be more common among those living in large cities in a similar study in Spain 29 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, according to this study, self-medication practices (SMP) have been found to be significantly associated with a person's residence, and the prevalence of SMP is higher among people living in rural areas than people living in urban areas. This is in contrast to a study in Ethiopia that revealed that living in a city was strongly associated with selfmedication 28 . SMP was shown to be more common among those living in large cities in a similar study in Spain 29 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, according to this study, self-medication practice (SMP) has been found significantly associated with a person’s residence, and the prevalence of SMP is higher among people living in the rural area than people living in urban areas. In contrast to a study in Ethiopia that revealed that living in a city was strongly associated with self-medication (28). SMP was shown to be more common among those living in large cities in a similar study in Spain (29).…”
Section: Discussioncontrasting
confidence: 83%
“…Five articles were included to examine the association between self-medication and income [ 24 , 31 , 32 , 34 , 38 ]. From those involved, two studies showed a significant association between income and self-medication [ 24 , 38 ].…”
Section: Resultsmentioning
confidence: 99%